Serving with a Smile on Airbnb: Analyzing the Economic Returns and Behavioral Underpinnings of the Host’s Smile - Zhang, Shunyuan; Friedman, Elizabeth M S; Srinivasan, Kannan; Dhar, Ravi; Zhang, Xupin (Journal of Consumer Research, 2025)
Abstract Non-informational cues, such as facial expressions, can significantly influence judgments and interpersonal impressions. While past research has explored how smiling affects business outcomes in offline or in-store contexts, relatively less is known about how smiling influences consumer choice in e-commerce settings when there is no face-to-face interaction. In this article, we use a longitudinal Airbnb dataset and a facial attribute classifier to quantify the effect of a smile in the host’s profile photo on property demand and identify factors that influence when a host’s smile is likely to have the biggest effect. A smile in the host’s profile photo increases property demand by 3.5% on average. This effect is moderated by a variety of host and property characteristics that provide evidence for the role of uncertainty underlying why smiling increases demand. Specifically, when there is greater uncertainty regarding either the quality of the accommodations or the interaction with the host, a host’s smile will have a greater effect on demand. Online experiments confirm this pattern, offering further support for uncertainty perceptions driving the effect of smiling on increased Airbnb demand, and show that the effect of smiling on demand generalizes beyond Airbnb.